Exploiting microwave scanning radar for monitoring Icelandic volcanic eruption source parameters - MEREU, LUIGI; MARZANO, FRANK SILVIO; MONTOPOLI, MARIO; Bonadonna C. (2014 11th European Radar Conference, 2014)
The explosive eruption at the summit of sub-glacial Ejyafjallajökull volcano in April-May 2010 was of modest size, but with a erupted ash plume reaching a 6-10 km height above the volcano vent. The ash was widely dispersed over Iceland and Europe, causing a global interruption of main air traffic and causing large economic losses. The quality of the airborne ash particle forecast in the atmosphere depends on realistic description of erupted ash dispersion and then on erupted fine ash mass rate. In this primary work, we present the validity of the use of microwave radar data to estimate mass flows rate MFR through an interesting extension of the Volcanic Ash Radar Retrieval (VARR), which uses the observables of C-band radar in Keflavik.